Analysis of Student Mistooks in Solving the Geometry Transformation Matter for Class IX SMPN 1 Geger Reviewed From The Stage of Polya Theory - Ridho Ariyanto Nanda Putra; Sanusi Sanusi; Darmadi Darmadi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2022)
Mathematics is considered a difficult subject because the concepts studied are not well understood, so that in solving math problems students often make mistakes. This study aims to analyze mistooks and factors causing mistooks made by class IX students of SMPN 1 Geger in terms of the stages of Polya's theory. This type of research is qualitative research. Data collection techniques used in the form of written tests and interviews. The research subjects used were 4 students of class IXB who were identified as making mistakes in solving problems in terms of the stages of Polya's theory. Data analysis techniques in this study used data reduction, data presentation, data verification and conclusions. The results of this study indicate that the mistooks made by the four subjects were (1) at the stage of understanding the problem students did not write down information about the questions. (2) at the stage of preparing the plan the students did not write the completion plan and the students could not determine the formula to be used. (3) at the stage of implementing the plan the students did not write down the completion steps or incorrectly applied the formula according to what was asked in the question. (4) at the re-checking stage, students do not re-check their answers or re-check but not systematically. The factors causing these mistooks are (a) students cannot understand the questions, (b) poor time management of students, (c) students' habits in solving problems.